2015
DOI: 10.7287/peerj.preprints.1464v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is there an association between elongation factor 1-α overdominance in the seastar Pisaster ochraceus and “seastar wasting disease”?

Abstract: View the peer-reviewed version (peerj.com/articles/1876), which is the preferred citable publication unless you specifically need to cite this preprint.Wares JP, Schiebelhut LM. 2016. What doesn't kill them makes them stronger:an association between elongation factor 1-α overdominance in the sea star Pisaster ochraceus and "sea star wasting disease". PeerJ 4:e1876 https://doi.org/10.7717/peerj.1876What doesn't kill them makes them stronger: An association between elongation factor 1-α overdominance in the sea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…We believe that, combined with research reported in other publications ([ 1 3 , 11 ], the study of SSWD exemplifies the approach advocated by Burge et al [ 12 ]: a “union of the modern and the classic” approaches to understanding marine diseases. For several reasons, the impact of disease on populations and communities is difficult to investigate [ 3 ].…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…We believe that, combined with research reported in other publications ([ 1 3 , 11 ], the study of SSWD exemplifies the approach advocated by Burge et al [ 12 ]: a “union of the modern and the classic” approaches to understanding marine diseases. For several reasons, the impact of disease on populations and communities is difficult to investigate [ 3 ].…”
Section: Introductionsupporting
confidence: 69%
“…Counterintuitively, during much of 2014 summer, susceptibility was lower in juveniles compared to adults ( Fig 3 , adults = 55.3 ± 2.6% vs. juveniles 3.9 ± 0.9%). The mechanistic basis for this apparent resistance is unclear and under investigation [ 1 , 11 ]. Possibilities could include: (1) higher frequencies of resistant genotypes or phenotypes among juveniles and recruits, (2) physiological differences between adults and small sea stars that make adults more susceptible to SSWD, (3) higher surface areas and larger volumes of water within the water vascular system in adults to “intercept” or retain water-borne pathogens, respectively, and (4) small size may make recruits harder to detect because they may die “faster.”…”
Section: Discussionmentioning
confidence: 99%